Do the media influence the judiciary? - Potter, M (2011)
As judges face growing criticism for 'disproportionate' sentencing of those convicted of inciting riots, Sir Mark Potter, former President of the Family Division of the High Court of England and Wales, assesses to what degree the media influence the judiciary. In the policy brief, he finds that judges generally remain impervious to outside influence, but that sentencing policy is sometimes influenced by public opinion.